The effect of educational exercises by stimulating the brain with (Fit Light) technique on improving functional thinking and some kinematic manifestations and learning to perform running (400) meters - Rossol kalaf (College of Physical Education and Sport Sciences, 2024)
The research aimed to prepare educational exercises to perform a 400-meter run by stimulating the brain with the Fit Light technology for students, and to identify the effect of these educational exercises by stimulating the brain with the Fit Light technique in improving functional thinking and some kinematic aspects of learning to perform a 400-meter run for students. The experimental research method was adopted by designing the experimental and control groups with tight control for the pre- and post-tests. The boundaries of the research community were represented by third-year students in the Department of Physical Education and Sports Sciences at Al-Mustafa University continuing the official working hours for the academic year (2023-2024), a total number of (85) students who were chosen. Among them for the main research sample were (40) students, representing (47.059%) from this community. Then, the experimental research group was randomly selected: students from Class (B), and students from Class (A) as a control group. After determining the measurement tools, an experiment was conducted by distributing (3) devices of (Fit Light) technology that operate with (LED) daylight or nightlight, distributed in arcs at distances of (100), (200), and (200) meters from the running track for an event of (400) meters, as the students applied it in the practical side of the main section for a period of (60) minutes of this lesson, at a rate of (2) lessons per week, for a period of (3) consecutive weeks. As for the students in the control group, they applied the same educational exercises, but without stimulating the brain with technology. (Fit Light), and the experiment began by applying pre-tests on Sunday, corresponding to (11/5/2023), and then the application began for the period extending from Monday, corresponding to (11/6/2023) until Wednesday, corresponding to (11/22). /2023), and the experiment ended with the application of post-tests on Thursday, corresponding to (11/23/2023), and the results were processed with the Social Statistical System (SPSS) so that the conclusions were recommendations that educational exercises by stimulating the brain with (Fit Light) technology help in improving functional thinking, In improving some of the kinematic aspects of both motor transfer between parts of the body and motor flow in terms of change in momentum, and in improving learning to run (400) meters among third-year students in the Department of Physical Education and Sports Sciences, it is necessary to increase the capabilities of athletics teachers to enable them to apply educational exercises. By stimulating the brain with Fit Light technology because of its important role in motor learning for both the mental and skill factor.